A Review of Acute and Long-Term Neurological Complications Following Haematopoietic Stem Cell Transplant for Paediatric Acute Lymphoblastic Leukaemia - Gabriel, Melissa; Hoeben, Bianca A. W.; Uhlving, Hilde Hylland; Zajac-Spychala, Olga; Lawitschka, Anita; Bresters, Dorine; Ifversen, Marianne (Frontiers in Pediatrics, 2021)
Despite advances in haematopoietic stem cell transplant (HSCT) techniques, the risk of serious side effects and complications still exists. Neurological complications, both acute and long term, are common following HSCT and contribute to significant morbidity and mortality. The aetiology of neurotoxicity includes infections and a wide variety of non-infectious causes such as drug toxicities, metabolic abnormalities, irradiation, vascular and immunologic events and the leukaemia itself. The majority of the literature on this subject is focussed on adults. The impact of the combination of neurotoxic drugs given before and during HSCT, radiotherapy and neurological complications on the developing and vulnerable paediatric and adolescent brain remains unclear. Moreover, the age-related sensitivity of the nervous system to toxic insults is still being investigated. In this article, we review current evidence regarding neurotoxicity following HSCT for acute lymphoblastic leukaemia in childhood. We focus on acute and long-term impacts. Understanding the aetiology and long-term sequelae of neurological complications in children is particularly important in the current era of immunotherapy for acute lymphoblastic leukaemia (such as chimeric antigen receptor T cells and bi-specific T-cell engager antibodies), which have well-known and common neurological side effects and may represent a future treatment modality for at least a fraction of HSCT-recipients.